2023
DOI: 10.3389/fimmu.2023.1118845
|View full text |Cite
|
Sign up to set email alerts
|

In-situ tumor vaccination by percutaneous ablative therapy and its synergy with immunotherapeutics: An update on combination therapy

Abstract: Percutaneous tumor ablation is now a widely accepted minimally invasive local treatment option offered by interventional radiology and applied to various organs and tumor histology types. It utilizes extreme temperatures to achieve irreversible cellular injury, where ablated tumor interacts with surrounding tissue and host via tissue remodeling and inflammation, clinically manifesting as post-ablation syndrome. During this process, in-situ tumor vaccination occurs, in which tumor neoantigens are released from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…Several clinical trials have shown that CIK cell-based immunotherapy increases RFS in HCC patients who have undergone surgical resection (reviewed on [ 181 ]). The 18-month recurrence rate after adjuvant CIK therapy was 15.6%, compared to 40.0% in the control group receiving ablation therapy alone [ 182 ].…”
Section: Non-classical Nkg2a Hla-e As a Novel Potential Checkpoint Ta...mentioning
confidence: 99%
“…Several clinical trials have shown that CIK cell-based immunotherapy increases RFS in HCC patients who have undergone surgical resection (reviewed on [ 181 ]). The 18-month recurrence rate after adjuvant CIK therapy was 15.6%, compared to 40.0% in the control group receiving ablation therapy alone [ 182 ].…”
Section: Non-classical Nkg2a Hla-e As a Novel Potential Checkpoint Ta...mentioning
confidence: 99%